THE DEVELOPMENT OF EDU COMIC TEACHING MATERIALS ABOUT HUMAN DIGESTIVE SYSTEM MATERIALS ON 5TH-GRADE ELEMENTARY SCHOOL - Nana Hendracipta; Seftiyanne Fauqy Hidayat; Lukman Nulhakim (JPSD (Jurnal Pendidikan Sekolah Dasar), 2020)
AbstractThis research is motivated by the needs for teaching materials that can explain human digestive system material concretely in the form of comics because with the combination of verbal and nonverbal language in comics can expedite students to understand the contents of the material. The purpose of this research is to describe how the process of developing teaching materials in the form of comics on the concept of the human digestive system for 5th-grade students of elementary schools. The research method used in this research is the research and development method. The data collection techniques used are literature studies and questionnaires, while the data were analyzed using descriptive analysis techniques by analyzing quantitative data and then interpreted in a qualitative. The results of research and development show that the process of comic teaching materials development on the material of the human digestive system goes through six stages namely data analysis, data collection, product design, product design validation, product improvement, and product trials. Moreover, the validity test of comic teaching materials on the concept of the human digestive system has a category of "very feasible" with design test results of 85%, material test results of 90%, and educational test results of 89.3%. While the trial results of 5th-grade students' responses were 88% and included in the criteria of "very good".Keywords: Teaching Material, Comic, Human Digestive System